Peran Kader Sosial Dalam Mendukung Proses Recovery Pada Orang Dengan Gangguan Jiwa Di Lembaga Kesejahteraan Sosial Sungai Ambawang Kuala Kabupaten Kubu Raya - Nadiyah, Afifah; Mardiyati, Isyatul; Irfani, Amalia (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2023)
Abstract: This study aims: To find out the activities carried out by social cadres in supporting theprocess Recovery for people with mental disorders, to find out the efforts made by social cadres in supporting theprocesswith Mental Disorders. Recovery for People Mental Disorders at Sungai Ambawang Kuala Social Welfare Institution, Kubu Raya Regency. In this study, the researcher used a qualitative approach with a descriptive type of research. Data collection techniques in this study are observation (observation), interviews (interviews), and documentation. The results of this study conclude that, the activities carried out by social cadres in supporting theprocess Recovery for ODGJ patients still include daily activities, such as guiding patients to carry out their personal needs independently and working together to clean up the surrounding environment. Efforts made by social cadres are bringing patients for check-up every month at Sungai Bangkong Hospital or Singkawang Hospital, giving medicine to patients, and building patient trust in social cadres by treating patients well, so that patients do not feel afraid and isolated.